Versatile synthesis of amino acid functionalized nucleosides via a domino carboxamidation reaction - Gheerardijn, Vicky; Van den Begin, Jos; Madder, Annemieke (Beilstein Journal of Organic Chemistry, 2014)
Functionalized oligonucleotides have recently gained increased attention for incorporation in modified nucleic acid structures both for the design of aptamers with enhanced binding properties as well as the construction of catalytic DNA and RNA. As a shortcut alternative to the incorporation of multiple modified residues, each bearing one extra functional group, we present here a straightforward method for direct linking of functionalized amino acids to the nucleoside base, thus equipping the nucleoside with two extra functionalities at once. As a proof of principle, we have introduced three amino acids with functional groups frequently used as key-intermediates in DNA- and RNAzymes via an efficient and straightforward domino carboxamidation reaction.
Keywords: amino acids; bioorganic chemistry; carboxamidation reaction; chemically modified; DNA nucleosides; nucleic acids